Tax Evasion and Swiss Bank Deposits - Niels Johannesen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2010)
Bank deposits in jurisdictions with banking secrecy constitute an effective tool to evade taxes on interest income. A recent EU reform reduces the scope for this type of tax evasion by introducing a source tax on interest income earned by EU residents in Switzerland and several other jurisdictions with banking secrecy. In this paper, we estimate the impact of the source tax on Swiss bank deposits held by EU residents while using that non-EU residents were not subject to the tax to apply a natural experiment methodology. We find that the 15% source tax caused Swiss bank deposits of EU residents to drop by more than 40% with most of the response occurring in two quarters immediately before and after the source tax was introduced. The estimates imply an elasticity of Swiss deposits with respect to the net-of-source-tax-rate in the range 2.5-3.
Keywords: 330; tax evasion; capital taxation; savings directive; Kapitalertragsteuer; Quellensteuer; Steuerwettbewerb; Steuerflucht; EU-Steuerrecht; EU-Staaten; Schweiz